Asymmetry between charge and discharge during high rate cycling in LiFePO4 - In situ X-ray diffraction study - Shin, Ho Chul; Chung, Kyung Yoon; Min, Won Sik; Byun, Dong Jin; Jang, Ho; Cho, Byung Won (ELSEVIER SCIENCE INC, 2008)
Asymmetric behavior of structural changes during charge and discharge of C-coated LiFePO4 has been investigated using synchrotron based in situ XRD. C-coated LiFePO4 undergoes phase transformation from triphylite to heterosite during charge and vise versa during discharge. However, it is observed that the phase transformation of C-coated Li1-xFePO4 during discharge is more difficult to be complete than that during charge. At 2C rate, the phase transformation from heterosite to triphylite was hardly observed during discharge while the complete phase transformation was observed in the previous charge. This indicates that the degree of the phase transformation completeness depends on the direction of the phase transformations. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: PHOSPHO-OLIVINES